EFEKTIVITAS INSTAGRAM SEBAGAI SARANA INFORMASI DAN PROMOSI PENGAJIAN MAJLIS TALIM SUBULUSSALAM - Andi Rosandi; Amanda Bunga Gracia (Universitas Prof. Dr. Moestopo (Beragama), 2020)
This research discusses the exposure of the information content of the Majlis Ta'lim Subulussalam communal recitation on Instagram and the effectiveness of promotion using the AISAS method. This research employed a survey method supported by the result of the quantitative data gathered from an online questionnaire. This study shows two important matters, such as the relationship resulted from the Spearman Rank test, and the effect resulted from the Simple Linear Regression Analysis.The first result entails a significant relationship between the exposure of the information on Instagram and the audiences Attention. There also is a noteworthy relationship between the exposure of the information on Instagram and the audiences Interest. Differently from the previous findings, it is shown that there is no significant relationship between the exposure of the information on Instagram and the behavior of Search for the communal recitation location. There is also not found any significant relationship between the behavior of audience to attend (Action). Additionally, there is no significant relationship on the behavior of Share because of the exposure of Instagram information. Secondly, there is no significant effect between the content information exposure on Instagrm (X) towards the promotion of the Majlis Ta'lim Subulussalam communal recitation (Y), it is proven by the finding of Sig. 0,110 0,05 and the positive effect gains only 4,9% which implies that the promotion effectiveness might be affected by other variables that were not studied in this research.